2021
DOI: 10.1021/acs.est.0c06407
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors of CO2 Hydrate Formation in the Presence of Acid-Dissolvable Organic Matters

Abstract: Carbon storage in the form of solid hydrate under seafloor has been considered to be promising for greenhouse gas control. Yet, open issues still remain on the role of the organic matters abundant in marine environments in the kinetics of hydrate formation; of particular interest is the involvement of the acid-dissolvable organic matters accompanying the acidification upon CO2 injection. In this work, the CO2 hydrate formation in the presence of the organic matters was in-situ monitored through the low-field n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…When CO 2 gas is dissolved in water, another consideration is the formation of carbonic acids that lower the pH of the aqueous phase. , One needs to consider that the solubility of the amino acids in liquid water can change with both temperature and pH under a given temperature and pressure condition. The pH of the CO 2 dissolved water at 273.15 K is estimated to be lowered to 3.18 and 4.04 with 35 bar and 1 bar of CO 2 gas, respectively, and the solubilities of amino acids (gly, l -ala, and l -val) can thus change accordingly …”
Section: Resultsmentioning
confidence: 99%
“…When CO 2 gas is dissolved in water, another consideration is the formation of carbonic acids that lower the pH of the aqueous phase. , One needs to consider that the solubility of the amino acids in liquid water can change with both temperature and pH under a given temperature and pressure condition. The pH of the CO 2 dissolved water at 273.15 K is estimated to be lowered to 3.18 and 4.04 with 35 bar and 1 bar of CO 2 gas, respectively, and the solubilities of amino acids (gly, l -ala, and l -val) can thus change accordingly …”
Section: Resultsmentioning
confidence: 99%
“…Because of these special physicochemical characteristics, NBs can be used for a wide variety of potential industrial applications in the biology, environment, medicine, and many other fields, such as mass transfer in gas hydrate researches. [ 11–15 ]…”
Section: Introductionmentioning
confidence: 99%
“…A number of measurements [ 6,10–16 ] have shown that NBs are indeed quite stable. However, there is a lack of widespread agreement on an explanation for the stability of both interfacial and bulk NBs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years, gas hydrates have received increasing attention. [24,25] Gas hydrate technology appears to be a promising method for gas separation and storage, energy storage, and seawater desalination based on the special characteristics of hydrates. [26][27][28][29][30] Gas hydrates are ice-like crystalline compounds in which water molecules form cavities by hydrogen bonds, and gas molecules are trapped in a stable manner in these cavities by van der Waals forces.…”
mentioning
confidence: 99%